THE EFFECT OF MEDICAL PERSONNEL COMPETENCE ON PATIENT SATISFACTION IN THE EMERGENCY DEPARTMENT OF ADAM MALIK GENERAL HOSPITAL, MEDAN - Harahap, Apriana; Asriwati, Asriwati; Nasution, Ramadhani Syafitri (HEARTY, 2026)
The Emergency Department (ED) is a critical unit in hospitals that requires high competence from medical personnel, as it is directly related to patient safety and satisfaction. This study aimed to analyze the effect of medical personnel competencencluding medical knowledge, professional attitude, clinical skills, communication ability, and decision-makingon patient satisfaction in the Emergency Department of Adam Malik General Hospital, Medan. This study employed a quantitative design with a cross-sectional approach involving 100 ED patients as respondents. Data analysis included validity and reliability tests, normality testing, bivariate analysis using the chi-square test, and multivariate analysis using logistic regression. The results showed that descriptively, the majority of respondents rated both medical personnel competence and patient satisfaction at a high level (87.6%). Bivariate analysis indicated that all competence variables were significantly associated with patient satisfaction (p < 0.05). However, multivariate analysis revealed that clinical skills (p = 0.033; OR = 2.820), professional attitude (p = 0.047; OR = 0.343), and communication ability (p = 0.035; OR = 0.367) had a significant effect on patient satisfaction. Meanwhile, medical knowledge (p = 0.203) and decision-making (p = 0.311) were not significantly associated. Clinical skills were identified as the most dominant factor influencing patient satisfaction In conclusion, higher competence of medical personnel, particularly in clinical skills, leads to increased patient satisfaction in the Emergency Department. It is recommended that hospitals continuously enhance medical personnel competence through emergency clinical training programs.